A Causal Relationship Model Between Characteristics, Knowledge, and Infection Prevention Behaviors for Coronavirus among Caregivers with End-Stage Renal Disease Patients Treated by Community Hospitals - Patiganmonthon, Namfon (NU Journal of Nursing and Health Sciences, 2025)
This quantitative research aim investigated the relationship model between caregivers’ characteristics (ages and durations for care), knowledge, and infection prevention behaviors for Coronavirus among caregivers of end-stage renal disease patients treated at community hospitals. The sample consisted of 150 caregivers for caregivers of end-stage renal disease patients selected using purposive sampling. Data were collected using a questionnaire with a content validity index of 0.94, a reliability coefficient for knowledge of 0.71 obtained through the Kuder-Richardson method, and a reliability coefficient for infection prevention behaviors for Coronavirus of 0.93 via Cronbach’s alpha. Data analysis was performed using descriptive statistics and path analysis. The results of this study were presented that the causal relationship between characteristics (ages and durations for care), knowledge, and infection prevention behaviors for Coronavirus among caregivers with end-stage renal disease patients was relevant with the empirical data (Chi-square = 1.00, GFI = 0.92, CFI = 0.94, NFI = 0.94, RMSEA = 0.00, RMR = 0.02). Caregivers’ characteristics (ages and durations for care) and their knowledge directly and indirectly affected to infection prevention behavior for Coronavirus, and 50% predictive power were presented. This study indicates that caregivers for end-stage renal disease patients is an important factor to infection prevention behaviors for Coronavirus. health services should support their understanding; therefore, caregivers can provide their care for End-Stage Renal Disease patients encountering with emerging infectious diseases in the future.